2014
DOI: 10.4103/0974-8520.153748
|View full text |Cite
|
Sign up to set email alerts
|

Clinical study on the efficacy of Rajayapana Basti and Baladi Yoga in motor disabilities of cerebral palsy in children

Abstract: Background:Cerebral palsy is a static encephalopathy that may be defined as a non-progressive disorder of posture and movement often associated with epilepsy and abnormalities in speech, vision and intellect resulting from a defect or lesion of the developing brain. There are 25 lakhs cerebral palsy affected children in India.Aim:To assess the efficacy of Rajayapana Basti (RB) and Baladi Yoga in motor disabilities of cerebral palsy in children.Materials and Methods:Total 98 children satisfying diagnostic crite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 5 publications
0
21
0
Order By: Relevance
“…For instance, shiromarma abhighataja due to akalapravahana vyadhi ie disease causing injury to brain has been seen to present with symptoms like loss of motor activities, difficulties in speech, hearing and vision, drooling of saliva, and improper coordination along with other functional difficulties. 10 Cerebral palsy as we understand today grossly presents with all or some of the above symptoms affecting those functions of the body corresponding to the site of the brain that is affected. Clinical trials have shown that Cerebral palsy is most effectively treated in the line of management of treatment of diseases caused due to vata (vatavyadhi chikitsa).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, shiromarma abhighataja due to akalapravahana vyadhi ie disease causing injury to brain has been seen to present with symptoms like loss of motor activities, difficulties in speech, hearing and vision, drooling of saliva, and improper coordination along with other functional difficulties. 10 Cerebral palsy as we understand today grossly presents with all or some of the above symptoms affecting those functions of the body corresponding to the site of the brain that is affected. Clinical trials have shown that Cerebral palsy is most effectively treated in the line of management of treatment of diseases caused due to vata (vatavyadhi chikitsa).…”
Section: Discussionmentioning
confidence: 99%
“…Vidarikanda, Godhuma, 26 and Yava. Yava is having both Madhura and Kashaya rasa while Vidarikanda and Godhuma with Madhura rasa only.…”
Section: Discussionmentioning
confidence: 99%
“…It has reported to possess anti-inflammatory, anticancer, antimalarial, antimicrobial, antidepressant, neuroprotective, free radical scavenging, immunomodulatory, spermatogenic, cardioprotective, hypocholesteremic, adaptogeneic and antioxidant properties. 40,41,45 Amalaki (Emblica officinalis Gaertn. )…”
Section: Ashwagandha (Withania Somnifera (L) Dunal)mentioning
confidence: 99%